Audit report lag in banks: A comparison between Islamic and conventional bank - Yusuf, Noora; Abdelhameed, Salwa; Janahi, Mohamed (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of this study is to empirically examine whether bank type matters in determining audit report lag (ARL). The study also aims to identify factors that determine audit report lag in Islamic banks and conventional banks. The study uses a sample of 297 bank-year observations from Islamic and conventional banks operating in Gulf Cooperation Council (GCC) countries during the years 2014–2021. Banks’ annual reports were used to gather the data. The findings show that Islamic banks have shorter audit delays than conventional banks. The findings also provide evidence on the relation between ARL and some corporate governance and bank characteristics (board of directors and audit committee size). Given the accelerated growth demonstrated by the Islamic banking industry, an examination of whether bank type (conventional or Islamic bank) and corporate governance mechanisms matter in determining ARL is warranted. This study extends the comparative literature (Islamic vs. conventional banks), being one of the first attempts to examine the role of bank type in determining ARL. The findings of this study could be beneficial to Islamic banks, conventional banks, external auditors, and regulators of banking institutions in the GCC, who seek enhanced financial reporting quality through the timely dissemination of information.